PERSEPSI WISATAWAN PADA PELAKSANAAN FOOD WALKING TOUR JAKARTA - Dian Rutz; Budiarto (LPPM and Travel Operation Department Universitas Asa Indonesia, 2020)
Culinary tourism is one of the creative economy subsectors with the dominant contribution to the gross domestic product. Its development, therefore, needs to be continuously encouraged. The Jakarta food traveler community is a pioneer in organizing food walking tours in Jakarta. Positive perception will affect the tourists' satisfaction, loyalty, and marketing of tourism products as well. This study aims to analyze tourist perceptions of the food walking tour. About 100 respondents participated to measure the tourist perception variable notably price, image, service stage, service moment, and implementation. The results showed that overall the tourists have a positive response to the food walking tour. Affordability of prices, a positive image of food walking tours as the only culinary tour package in Jakarta, the competence of tourist guides are important factors affecting the positive tourist perceptions